Effects of Lunar Phases on Foot Temperature, Oxidative Stress, and Inflammation in Type 2 Diabetic Subjects - Bhattacharjee, Koena; Pramanik, Subhasish; Chowdhury, Sutanu D.; Basu, Barnali Ray; Mondal, Lakshmi Kanta (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Background: It has been observed that the lunar phases alter the fasting plasma glucose (FPG) level in type-2 diabetic (T2DM) subjects. Diabetic peripheral neuropathy (DPN) was also reported to be associated with elevated foot temperature (FT), oxidative stress, and inflammation in T2DM subjects. Objectives: The purpose of the present study was to evaluate the changes in FT, oxidative stress, and inflammation levels and assess the relationship of FT with oxidative stress, antioxidant enzyme activity, and inflammatory markers in T2DM subjects at different lunar phases. Methods: The plasma glucose, glycated hemoglobin, and dorsal and plantar surface temperatures of the feet by infrared dermal thermometer were measured in 88 randomly selected T2DM subjects at different lunar phases. The levels of oxidative stress and inflammation were assessed by measuring malondialdehyde (MDA), glucose 6-phosphate dehydrogenase (G6PDH), and tumor necrosis factoralpha (TNF-α). Results: The FTs, MDA, and TNF-α were significantly increased, and G6PDH activity was significantly decreased in the new moon (NM) and full moon (FM) than in the third quarter (TQ) and first quarter (FQ) for both sexes. The FTs, MDA, and TNF-α levels were significantly positively correlated, whereas G6PDH activity was significantly negatively correlated with FPG at NM and FM in both sexes. The MFT was significantly positively correlated with MDA and TNF-α and significantly negatively correlated with G6PDH at NM and FM in T2DM subjects. Conclusion: The lunar phases showed a prominent influence on the FT, oxidative stress, and inflammatory status in T2DM subjects, which might be due to the existence of biological rhythm interaction with lunar electromagnetic radiations.
Keywords: Lunar phases